The complete guide to plumbing. (Cool Springs Press, an imprint of The Quarto Group, 2019)
"From fixing a toilet to installing and plumbing a vanity sink or curbless shower, BLACK+DECKER The Complete Guide to Plumbing Updated 7th Edition has the answer to any home plumbing problem you're likely to have. Packed with clear color photos and easy-to-understand descriptions, the basics of home plumbing systems are clearly explained, and all of the most popular plumbing projects are shown with clear, color step-by-step photos. This new edition has been thoroughly updated to ensure that all information conforms to the most recent codes, including the 2018 Uniform Plumbing Code and the 2018 International Residential Code."--Amazon.com.